A self‐help coping intervention can reduce anxiety and avoidant health behaviours whilst waiting for cancer genetic risk information: results of a phase III randomised trial. Issue 4 (4th April 2012) - Phelps, Ceri; Bennett, Paul; Hood, Kerenza; Brain, Kate; Murray, Alexandra
Abstract Objective The objective of this study is to evaluate the effectiveness of a self‐help coping intervention in reducing intrusive negative thoughts while waiting for cancer genetic risk information. Methods Between August 2007 and November 2008, 1958 new referrals for cancer genetic risk assessment were invited to participate in a randomised trial. The control group received standard information. The intervention group received this information plus a written self‐help coping leaflet. The primary outcome measure was the intrusion subscale of the Impact of Event Scale. Results The intervention significantly reduced intrusive thoughts during the waiting period in those reporting moderate baseline levels of intrusion (p = 0.03). Following risk provision, those in the intervention group reporting low and moderate intrusive worries at baseline reported less intrusive thoughts than those in the control group (p = 0.04 and p = 0.03, respectively). The intervention had no adverse impact in the sample as a whole. Participants in the intervention group with high baseline avoidance and negative affect scores were significantly more likely to remain in the study than those in the control group (p = 0.05 and p = 0.004). Conclusions Findings that the intervention both reduced distress in those with moderate levels of distress and had no adverse effects following notification of cancer genetic risk suggest that this simple intervention can be implemented across a range of oncology settings involving periods of waiting and uncertainty. The intervention may also reduce the number of individuals dropping out of cancer genetic risk assessment or screening. However, those with clinically high levels of psychological distress are likely to require a more intensive psychological intervention. Copyright © 2012 John Wiley & Sons, Ltd.